The Chinese Economies in Global Context: The Integration Process and Its Determinants - Yin-Wong Cheung; Menzie Chinn; Eiji Fujii (University of California, Economics Department, 2003)
The linkages between the People's Republic of China and the other Chinese economies of Hong Kong and Taiwan are assessed, and compared against those with Japan and the US. We first characterize the time series behavior of three criteria of integration, namely real interest parity, uncovered interest parity, and relative purchasing power parity. There is evidence that these parity conditions tend to hold over longer periods between the People's Republic of China and all other economies, although they do not hold instantaneously. Overall, the magnitude of deviations from the parity conditions is shrinking over time. Amongst all, however, Hong Kong exhibits indications of a more advanced level of integration with the mainland. We also find that evidence is surprisingly positive for integration with the US. We then turn to examining the determinants of the degree of integration. Regression results suggest that the degrees of financial and integration depend upon the extent of capital controls, foreign direct investment linkages as well as exchange rate volatility.
Keywords: 330; uncovered interest parity; real interest parity; purchasing power parity; exchange rates; capital mobility; market integration